Urgensi Penyerapan Nilai Hukum Islam dan Hukum Adat dalam Pengaturan Tindak Pidana Perzinaan - Usman Usman; Sri Rahayu; Elizabeth Siregar (Fakultas Hukum Universitas Jambi, 2021)
Reflecting on the impact of adultery, adultery is a despicable act that deserves to be criminalized. Even so, the prohibition on adultery in Article 284 of the Criminal Code does not cover every form of adultery as in the view of the law that lives in society as reflected in Islamic and customary laws. The model for the formulation of the criminal act of adultery in the 2019 Criminal Code Bill has adopted the definition of adultery from the law that lives in society, although it does not yet view the perpetrator's marital status and pregnancy as burdensome elements. Likewise, it does not criminalize women who with their consent commit adultery because of trickery, and lightly penalize the perpetrators of living together as a family without being married. Therefore, the model for the formulation of the criminal act of adultery in the upcoming Criminal Code Bill should take into account: a) the marital status of the perpetrator and pregnancy as elements that are burdensome for the crime; b) a woman who with her consent commits adultery because of a trick is both a victim and a perpetrator so that she can be convicted; c) persons who live together as husband and wife outside of marriage should receive a heavier punishment than the basic form of adultery. Abstrak Bercermin dari dampak perzinaan, maka perzinaan merupakan perbuatan tercela yang pantas dikriminalisasi. Meskipun demikian, larangan perzinaan dalam Pasal 284 KUHP belum mencakup setiap bentuk perzinaan sebagaimana dalam pandangan hukum yang hidup dalam masyarakat yang tercermin dari hukum Islam dan hukum adat. Model perumusan tindak pidana perzinaan dalam RUU KUHP tahun 2019 telah mengadopsi definisi zina dari hukum yang hidup dalam masyarakat, meskipun belum memandang status perkawinan pelaku dan kehamilan sebagai unsur yang memberatkan. RUU juga tidak mengkriminalisasi perempuan yang dengan persetujuannya melakukan perzinaan karena tipu muslihat, dan memidana ringan pelaku hidup bersama sebagai keluarga tanpa nikah. Oleh karena itu model pengaturan tindak pidana perzinaan dalam RUU KUHP mendatang sebaiknya memerhatikan: a) status perkawinan pelaku dan kehamilan sebagai unsur yang memberatkan pidana; b) perempuan yang dengan persetujuannya melakukan perzinaan karena tipu muslihat merupakan korban sekaligus pelaku sehingga dapat dipidana; c) orang yang melakukan hidup bersama sebagai suami istri di luar perkawinan seharusnya mendapat pidana lebih berat dibanding jenis perzinaan dalam bentuk pokok.